Using the Theory of Conceptual Metaphor to Understand Utterance Metaphorical in English Version of Surah An-Nisa - Usmala Dewi Siregar; Syahron Lubis; Khairina Nasution (RETORIKA: Jurnal Ilmu Bahasa, 2021)
This study discusses the results of the analysis performed to determine the meaning of the metaphor in the Surah An-Nisa English version. This study is carried by applying a systematic method. Through the observation method followed by the note-taking technique, researchers identified the Quran Surah An-Nisa English Version 176 verses to find metaphors and analyzed the data with understanding the meaning of each utterance that appeared by finding keywords from the source domain of the lexicon and the target domain in one metaphorical. The results of data analysis were presented through formal and informal methods. The findings are abstract meaning that are constructed more concrete by God as guidance to humans through metaphorical utterances. The implication of this study helps people to understand the messages of the verse in the Quran, especially the Surah An-Nisa.